Analisis faktor-faktor yang mempengaruhi kualitas manajemen risiko operasional di bank syariah: Studi literatur - Fadlilah, Lailatul Iftitachatil (Maliki Interdisciplinary Journal, 2024)
This article aims to provide insights on how operational risk can affect the sustainability and long-term viability of Islamic banking, as well as to find out the factors and strategies that can be taken by Islamic banking to manage operational risk properly and efficiently. This article identifies that operational risk can arise from internal factors of Islamic banking, human error, system or IT failure, and external factors. In addition, this article also outlines risk management strategies that can be implemented by Islamic banking which can be done by identifying, assessing, responding to risks, implementing, and evaluating. Thus, through this strategy, it is hoped that Islamic banking institutions can continue to determine the operational risk management used for institutions properly and efficiently. This article also contributes to the sustainability and sustainability of Islamic banking in Indonesia and the world.